An empirical approach for software reengineering process with relation to quality assurance mechanism - Muzammul, Muhammad; Awais, Muhammad (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2018)
Software development advances focus on productivity of existing software systems and quality is the basic demand of every engineering product. In this paper, we will discuss the complete re-engineering process with aspects of forwarding, reverse and quality assurance mechanism. As we know the software development lifecycle (SDLC) follows a complete mechanism of the engineering process. In forward engineering, we tried to follow selective main phases of software engineering(data,requirements, design, development, implementation).In reverse engineering, we move backward from the last phase of developing the product as it gathers requirements from the implemented product(implementation, coding, design, requirements, data). During reengineering, we add up more quality features on customer demands, but the actual demand is to fulfill quality needs that can be assured by external as well as internal quality attributes such as reliability, efficiency, flexibility, reusability, and robustness in any software system. We discussed a methodological approach to move from re-engineering to the journey of quality assurance. More than 50 studies come into discussion and throughput results proposed by graph and tabular form. We can say if the re-engineering process produces quality attributes, then it can be said by old software system refactoring as code refactoring, data refactoring and architectural refactoring we obtained a quality product at a lower cost instead of new software system development, which causes a decrease in quality attributes as cost, time etc. In future work, testing methodology can be proposed for quality assurance.